1992
DOI: 10.1128/mcb.12.6.2545
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency germ line gene conversion in transgenic mice.

Abstract: Gene conversion is the nonreciprocal transfer of genetic information between two related genes or DNA sequences. It can influence the evolution of gene families, having the capacity to generate both diversity and homogeneity. The potential evolutionary significance of this process is directly related to its frequency in the germ line. While measurement of meiotic inter-and intrachromosomal gene conversion frequency is routine in fungal systems, it has hitherto been impractical in mammals. We have designed a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 40 publications
4
34
1
Order By: Relevance
“…Gene conversion events also appeared to occur at multiple developmental stages, in both mitotic and meiotic cells, with the overall contribution to variation in sperm genotypes being potentially much greater for mitotic events. Notably, one other study of gene conversion in the mouse germ line has been undertaken, and it was reported that as many as 2% of spermatids were recombinant (34). Comparable substrates in our study, the stabilized transgenes with interrupted palindromes, undergo recombination at least at a 20-fold-reduced rate.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Gene conversion events also appeared to occur at multiple developmental stages, in both mitotic and meiotic cells, with the overall contribution to variation in sperm genotypes being potentially much greater for mitotic events. Notably, one other study of gene conversion in the mouse germ line has been undertaken, and it was reported that as many as 2% of spermatids were recombinant (34). Comparable substrates in our study, the stabilized transgenes with interrupted palindromes, undergo recombination at least at a 20-fold-reduced rate.…”
Section: Discussionmentioning
confidence: 87%
“…In each case, one or more copies had apparently undergone recombination within the lacZ repeats prior to integration (data not shown). In this, our experience was not unusual; we and others have previously detected recombination of DNA injected into fertilized eggs (33,34). Because the transgenic sequences in these other founders were already recombinant, the mice were not further analyzed for gene conversion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MHC class I genes may simply provide a unique opportunity to visualize these recombination events, because they result in functional changes in the antigen-presenting properties of the encoded molecules, which can be selected by an immunological reaction. Visualization of variants in other gene families would require molecular assays capable of screening thousands of individuals or an analysis that can take advantage of the individual nature of germ-line cells such as spermatozoa (23). Approaches of this kind also would permit similar analyses to be conducted in other species, such as humans, where screening large numbers of genetically typed animals is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Aspects of the relationship between meiotic recombination and homolog pairing are revealed by studies of ectopic recombination (20)(21)(22)(23)(24). Ectopic recombination occurs during S. cerevisiae meiosis but is limited by chromosomal context.…”
mentioning
confidence: 99%